1967
DOI: 10.1083/jcb.35.2.303
|View full text |Cite
|
Sign up to set email alerts
|

Filament Ultrastructure and Organization in Vertebrate Smooth Muscle

Abstract: Using a variety of preparative techniques for electron microscopy, we have obtained evidence for the disposition of actin and myosin in vertebrate smooth muscle. All longitudinal myofilaments seen in sections appear to be actin. Previous reports of two types of longitudinal filaments in sections are accounted for by technical factors, and by differentiated areas of opacity along individual filaments. Dense bodies with actin emerging from both ends have been identified in homogenates, and resemble Z discs from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
15
0
1

Year Published

1970
1970
1979
1979

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(16 citation statements)
references
References 20 publications
0
15
0
1
Order By: Relevance
“…Direct counts of actin filaments reveal also that they are more abundant than filaments containing myosin: values of 15-60:1 are reported (43,50), although this particular issue is complicated by the difficulty in preserving the myosin-containing filaments in smooth muscle. Determining the abundance and distribution of the myosin filaments has been a subject of considerable difficulty in recent studies (28,40,44,50). The class of filaments with the largest diameter were earlier assumed to contain myosin only because of their overall resemblance to the thick myosin-containing filaments in striated muscles and because of the similarity in the form of "synthetic" filaments made from the myosin from both smooth and striated muscle (5,12,30,39).…”
Section: Peter Cooke Filamentous Cytoskeleton 551mentioning
confidence: 99%
See 1 more Smart Citation
“…Direct counts of actin filaments reveal also that they are more abundant than filaments containing myosin: values of 15-60:1 are reported (43,50), although this particular issue is complicated by the difficulty in preserving the myosin-containing filaments in smooth muscle. Determining the abundance and distribution of the myosin filaments has been a subject of considerable difficulty in recent studies (28,40,44,50). The class of filaments with the largest diameter were earlier assumed to contain myosin only because of their overall resemblance to the thick myosin-containing filaments in striated muscles and because of the similarity in the form of "synthetic" filaments made from the myosin from both smooth and striated muscle (5,12,30,39).…”
Section: Peter Cooke Filamentous Cytoskeleton 551mentioning
confidence: 99%
“…When methods of preparation affording high resolution were developed, the myofilaments were found to constitute a single class with a diameter of 60-80 A that corresponds to the contractile protein F-actin (24,48). There was no evidence that myosin was present in filamentous form (13,40), although this protein could be isolated and induced to form filaments in vitro (25,29,48). Further work established that filaments resembling the myosin-containing filaments in striated muscles could be found in experimentally treated smooth muscle (5,30,39) and, more recently, when smooth muscles were fixed under "physiological" conditions, numerous thick myofilaments and X-ray reflections characteristic of myosin filaments were found (8,12,21,34,44,50).…”
mentioning
confidence: 99%
“…Several recent reports from three different groups (2)(3)(4)(5), who found both thick and thin filaments in sections of smooth muscle by electron microscopy, strongly indicated that a mechanism of sliding between thick and thin filaments may operate in smooth muscle as well as striated muscle . One team failed to find thick filaments but instead claimed to have located myosin molecules in sections, and proposed a sliding mechanism involving myosin dimers (6,7) . X-ray diffraction studies (8,40) have generally failed to detect myosin thick-filament reflections, although one study on guinea pig taenia coli did find evidence for ordered arrays of thin filaments (9) .…”
Section: Introductionmentioning
confidence: 99%
“…Another explanation for the presence of only thin filaments could reside in the functional state of the endothelium at time of fixation, since it has recently been shown that relaxed smooth muscle contains solely actin filaments (11) . The possibility of actin-myosin interaction is not precluded, however, by the absence of myosin-like filaments, for there is some evidence that myosin in living smooth muscle may exist in a relatively disaggregated form that is still able to promote the sliding of interdigitated actin filaments (17) . In this regard, actomyosin that is antigenically similar to that of uterine smooth muscle has recently been demonstrated in vascular endothelium by the fluorescent antibody technique (1) .…”
Section: Observations and Discussionmentioning
confidence: 99%